Evaluasi Kebijakan Penanganan Konflik Sunni-Syiah Di Sampang: Analisis Surat Keputusan Gubernur Jawa Timur No. 55 Tahun 2012 - Chabib Musthofa (Universitas Islam Tribakti Lirboyo Kediri, 2023)
East Java Governor Decree No. 55/2012, which regulates the Development of Religious Activities and the Supervision of Cults, is a response to various religious events in East Java society. This regulation emerged as a result of the physical conflict between Sunni and Shia communities in Sampang Regency, Madura, which resulted in the loss of life and material from both parties involved. One of the implementations of this policy is the relocation of Sampang Shia followers to Jemundo Flat in Sidoarjo, and until now, some of them have not returned to Sampang. In the context of the Sampang Sunni-Shiite conflict, this regulation has been more curative than preventive in its implementation for almost a decade, and from the perspective of public policy discipline, several issues still need to be addressed. This study uses a qualitative approach with observation techniques, in-depth interviews, and document analysis accompanied by triangulation. The results show that the implementation of this regulation has contributed to the search for a resolution in the Sunni-Shiite conflict, although there are still imbalances in some aspects. In particular, given the sensitivity of the Sunni-Shia conflict phenomenon, especially in the local context of Sampang, this imbalance is seen in the historical, political, bureaucratic, and sociological dimensions. Therefore, it can be concluded that this regulation is a policy that can be evaluated and has provided results in conflict resolution efforts, but also requires a review to address the imbalances that still exist.